Flexible Poly(Amide‐Imide)‐Carbon Black Based Microheater with High‐Temperature Capability and an Extremely Low Temperature Coefficient. (26th April 2016) - Liparoti, Sara; Landi, Giovanni; Sorrentino, Andrea; Speranza, Vito; Cakmak, Mukerrrem; Neitzert, Heinz Christoph
Abstract : Flexible poly(amide‐imide)‐carbon black (PAI‐CB) composite films, to be applied as high performance microheater foil, have been prepared with a solution/casting technique. The CB dispersion has been carefully controlled in order to improve the thermal and electrical properties of the resulting composites. Morphology and structure of the PAI‐CB composite films have been characterized by optical microscopy, atomic force microscopy and FTIR spectroscopy. The effect of the CB dispersion and its interaction with the polymer chains on the thermal and mechanical properties of the composite films have been investigated by using differential scanning calorimetry thermogravimetric analysis and dynamic mechanical analysis. The electrical characterization has evidenced high‐temperature capability and an extremely low temperature coefficient of the electrical resistance. An excellent ohmic behavior of the electrical characteristics and a fast on/off‐switching of the heater‐foil have also been found. No mechanical and electrical changes of the polymeric heater have been observed after various mechanical bending cycles. The combination of the observed electrical and thermal properties allows the realization of stable, compact, and flexible electrical heating systems. Abstract : The preparation and characterization of a new flexible poly(amide‐imide)‐carbon black heater with high thermomechanical resistance and an extremely low temperature coefficient is reported. A deep investigation of the electrical and mechanical properties demonstrates both the stability of the nanocomposite to high temperatures and unexpected zero temperature coefficient.